The Mathematical Impoverishment of Recommendations for Teaching in Official Physics Textbooks at High-School Level [el Empobrecimiento Matemático de Las Propuestas de Enseñanza de Física en Los Textos Oficiales de Secundaria] - Espinoza-Salfate, L; Barbe-Farre, J (Universitat Autonoma de Barcelona, 2017)
This article presents an analysis of physics textbooks for 7th-grade primary school and 2nd-grade high-school students (aged 11 to 15 years) in Chile. The didactical structuring of the teaching units displayed in the textbooks is analyzed with aim of identifying curricular features that hinder the students transition from primary school (grades 1 to 8) to high-school (grades 1 to 4) and that obstruct the expected learning achievements declared in the study programs. The research is embedded in the theoretical framework of Anthropological Theory of Didactics (Chevallard 1999), particularly important is its concept of «praxeology». Based on the result of the analysis, the article establishes a didactical phenomenon to be named «the demathematisation of recommendations for the teaching of high-school physics» in Chile. We believe that this is not an isolated event in Chile and a more common didactical phenomenon, as already mentioned by Chevallard (2013).